2023
DOI: 10.3342/kjorl-hns.2022.00227
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Score, Radiological Examination, and Nasopharyngeal Endoscopy in Adenoid Hypertrophy Patients as a Consideration of Adenoidectomy

Abstract: IntroductionAdenoids are part of the ring of waldeyer and have a role in the body's defense function. 1,2) Symptoms of adenoid hypertrophy include rinolalia occlusal, mouth open to breathe, adenoid face, nasal aprosexia, headache, runny nose, chronic cough, decreased appetite, and reduced hearing. The adenoids become hypertrophied in pathological conditions that often occur in children, which can cause complications in nasal obstruction, snoring, sleep apnea, otitis media, and affect the craniofacial shape. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Based on the results of this study, it was found that adenoid and adenotonsillar hypertrophy occurs more frequently in males 57,1% and 51,6%. These results are in line with previous research on adenoid hypertrophy patients in Universitas Airlangga Hospital for the period 2019-2021, which reported 46 (63%) males and 27 (37%) females (Nugroho et al, 2023). Another study by Yaseen, Khammas, and Anbaky found that there were 81 (54%) male patients and 69 (46%) female patients (Yaseen, Khammas and Anbaky, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the results of this study, it was found that adenoid and adenotonsillar hypertrophy occurs more frequently in males 57,1% and 51,6%. These results are in line with previous research on adenoid hypertrophy patients in Universitas Airlangga Hospital for the period 2019-2021, which reported 46 (63%) males and 27 (37%) females (Nugroho et al, 2023). Another study by Yaseen, Khammas, and Anbaky found that there were 81 (54%) male patients and 69 (46%) female patients (Yaseen, Khammas and Anbaky, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…As presented in table 2, it is known that the highest percentage are 42,9% and 58,1% within the age range of 5-11 years. The previous research on adenoid hypertrophy patients in Universitas Airlangga Hospital during the period 2019-2021 indicated that the majority of patients were aged 6-10 years (Nugroho et al, 2023). A total of 38% of adenoid hypertrophy patients in the 2021 study were in the age group of 6-8 years (O et al, 2021).…”
Section: Discussionmentioning
confidence: 96%